2001
DOI: 10.1161/01.cir.103.8.1102
|View full text |Cite
|
Sign up to set email alerts
|

Bundle-Branch Reentry and the Postpacing Interval After Entrainment by Right Ventricular Apex Stimulation

Abstract: Background-Diagnosis of bundle-branch reentry ventricular tachycardia (BBR-VT) by the standard approach is challenging, and this may lead to nonrecognition of this tachycardia mechanism. Because the postpacing interval (PPI) after entrainment has been correlated with the distance from the pacing site to the reentrant circuit, BBR-VT entrainment by pacing from the right ventricular apex (RVA) should result in a PPI similar to the tachycardia cycle length (TCL). This factor may differentiate BBR-VT from other me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Merino et al reported that a difference of <30 ms between PPI and tachycardia CL by entrainment pacing from the RVA was suggestive of BBRVT. 3 Furthermore, the CL of the InterFVT was longer than that of the BBRVT in the present case. Since the conduction in the LPF and LAF was slow due to extensive anterior MI, apparently shorter circuit of the InterFVT yielded a longer CL.…”
mentioning
confidence: 39%
“…Merino et al reported that a difference of <30 ms between PPI and tachycardia CL by entrainment pacing from the RVA was suggestive of BBRVT. 3 Furthermore, the CL of the InterFVT was longer than that of the BBRVT in the present case. Since the conduction in the LPF and LAF was slow due to extensive anterior MI, apparently shorter circuit of the InterFVT yielded a longer CL.…”
mentioning
confidence: 39%
“…4) were defined as sharp, high-frequency potentials preceding the QRS onset during sinus rhythm. Bundle branch re-entry was ruled out by standard criteria (12). …”
Section: Methodsmentioning
confidence: 99%
“… Idiopathic VT Sites Right ventricular outflow tract and pulmonary arteryLeft ventricular outflow tractAortic cuspsMitral and tricuspid annulusEpicardial basal VTIntrafascicular verapamil-sensitive reentrant tachycardiaPapillary muscles 120 Mapping techniques 121 Activation mapping and pace-mappingIdentification of Purkinje potentials, entrainment mappingApproach: Transvenous right ventricular, retrograde aortic, transseptal, coronary venous system, percutaneous epicardial approach Catheter ablation for non-ischemic cardiomyopathy 122,123 Myocardial VT Mechanism: Reentry within the myocardiumLocation: Basal left ventricle, epicardium, right ventricleAblation: Guided by pace-mapping, entrainment mapping, isolated potentialsBundle branch reentry 124 Generally occurs in patients with diffuse conduction system diseaseRole of different maneuvers, comparison of HH and VV intervals, postpacing interval Catheter ablation of post-infarction VT 125,126 Most appropriate as palliative therapy for frequent VT in patients with implantable defibrillatorsPotential role for prevention of ICD dischargesMechanism is reentry using surviving myocytes within scar tissueMapping: Entrainment if hemodynamically tolerated, pace-mapping for non-tolerated VTs, identification of isolated potentials Catheter ablation of frequent PVCs in patients with cardiomyopathy 127 and PVC-induced ventricular fibrillation (VF) or polymorphic VT 128 Recognize the relation of frequent PVCs in cardiomyopathy that is reversible with radiofrequency ablation. Ventricular fibrillation or polymorphic VT triggered by PVCs can be controlled by ablation of the initiating PVCs.…”
Section: Ablation Of Vtmentioning
confidence: 99%
“…Catheter ablation for non-ischemic cardiomyopathy 122,123 Myocardial VT Mechanism: Reentry within the myocardiumLocation: Basal left ventricle, epicardium, right ventricleAblation: Guided by pace-mapping, entrainment mapping, isolated potentialsBundle branch reentry 124 Generally occurs in patients with diffuse conduction system diseaseRole of different maneuvers, comparison of HH and VV intervals, postpacing interval…”
Section: Ablation Of Vtmentioning
confidence: 99%
See 1 more Smart Citation